2016
DOI: 10.1515/cjf-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the biology of Abu mullet Liza abu (Heckel, 1843) in the Orontes River, Turkey

Abstract: The age, growth and reproduction are described for 411 individuals of abu mullet from the Orontes River in Turkey between May 2011 and April 2012. The overall male to female ratio was 1:1.29. Fork length of all individuals ranged from 2.2 to 18.5 cm and total weight from 1.85 to 66.40 g. Isometric growth was observed for males (b=2.938) and all individuals (b=2.907); positive allometric growth was observed for females (b=3.246). The von Bertalanffy growth parameters based on data from otoliths were L ∞ = 19.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The sex ratio in this study was equal (1M:1F), however, it differed in different seasons and length classes. In other studies, the sex ratio of P. abu was reported as 1M:2.7F in Khozestan Province, Iran (Chelemal et al, 2009), as equal in Atatürk Dam Lake (Doğu et al, 2013) and as 1M:1.3F in the Orontes River, Turkey (Ay and Özcan, 2016). These differences are most probably related to sexual differences in growth rate, natural mortality rate, and energetic cost of reproduction (Stergiou et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The sex ratio in this study was equal (1M:1F), however, it differed in different seasons and length classes. In other studies, the sex ratio of P. abu was reported as 1M:2.7F in Khozestan Province, Iran (Chelemal et al, 2009), as equal in Atatürk Dam Lake (Doğu et al, 2013) and as 1M:1.3F in the Orontes River, Turkey (Ay and Özcan, 2016). These differences are most probably related to sexual differences in growth rate, natural mortality rate, and energetic cost of reproduction (Stergiou et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
“…In this study, the maximum observed total length and weight of P. abu was 17.3 cm and 71.28 g, respectively. In other studies, the maximum reported fork length and weight is 22.1 cm and 136.6 g in Atatürk Dam Lake (Doğu et al, 2013), 22 cm and 66.1 g in East Hammar marsh of Iraq (Mohamed, 2014) and 18.5 cm and 66.40 g in the Orontes River, Turkey (Ay and Özcan, 2016), 65.0 cm (Garbin et al, 2014) in southeastern coastal regions of Brazil and 23.1 cm and 166.1 g in Ceyhan River Basin of Turkey (Birecikligil et al, 2017). In general, the differences in the length of the fish could be due to differences in the fishing methods and seasons, different geographic areas, biological and ecological conditions, or inter-species differences.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations